Hands-On Data Analysis with NumPy and Pandas : Implement Python Packages from Data Manipulation to Processing - Miller, Curtis (Packt Publishing Ltd, 2018)
Chapter 3: Operations on NumPy Arrays; Selecting elements explicitly; Slicing arrays with colons; Advanced indexing; Expanding arrays; Arithmetic and linear algebra with arrays; Arithmetic with two equal-shaped arrays; Broadcasting; Linear algebra; Employing array methods and functions; Array methods; Vectorization with ufuncs; Custom ufuncs; Summary; Chapter 4: pandas are Fun! What is pandas?; What does pandas do?; Exploring series and DataFrame objects; Creating series; Creating DataFrames; Adding data; Saving DataFrames; Subsetting your data; Subsetting a series; Indexing methods.